New dawn or end of labour?: from South Africa's East Rand to Ekurhuleni. Issue 2 (17th February 2020) - Webster, Edward; Englert, Thomas
ABSTRACT: The question raised in this article is whether the key role played under apartheid by labour in the transition to democracy can be revived in the struggle against the persistent and deepening inequality of the post-apartheid period. We argue that the transition to a neoliberal state in the post-apartheid period has fragmented workers and weakened their capacity to build sustainable workplace organization. However, in spite of this, we identify the emergence of collective action and organization amongst these precarious workers. We show how in response to the degeneration of their traditional organizations, these workers are rebuilding worker organization still very much inscribed in the organizational traditions built on the East Rand over 40 years ago. We challenge the pessimistic 'end of labour' thesis that suggests that the informalization of employment has made collective organization impossible.